Concrete Neville's insights and issues - Neville, Adam M. (Thomas Telford, 2006)
Adam Neville is a world expert on concrete technology. In this book he demonstrates his radical thinking through incisive reflections and forecasts. He looks at a problem or an issue, and discusses the underlying scientific and technological aspects, including broader contextual topics.
Keywords: Concrete.; Concrete construction.; elektronické knihy; electronic books